Hermeneutic Methods in Understanding the Works of Alisher Navoi - Tajibayeva Ozoda Taxirovna (International Journal Of Literature And Languages, 2025)
It is also drawn attention to adjust the interpretation of the works of changes in attitude to the works of art, the analysis of the level of understanding of the classical works of the reader. The characteristic features of that period, according to the needs of readers reviews were transformed into prose, carried out by analyzing changes in the first prose description of "Nasri Xamsai unique" case-lit. There were analyzed the original interpretation of the work, which shows the mistakes and flaws.